DEVELOPMENT OF ILMUONE CLOUD AS A LEARNING RESOURCE AT SMK MUHAMMADIYAH 6 LEUWILIANG: A LITERATURE STUDY - Amelia, Tasya; Fatimah, Siti (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2026)
This research aims to develop and examine IlmuOne Cloud as a Learning Management System (LMS) to improve the effectiveness and flexibility of online learning at SMK Muhammadiyah 6 Leuwiliang. The study focuses on addressing the limitations of conventional classroom-based instruction, particularly restricted access to learning materials and the absence of real-time evaluation. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. Data were collected through literature analysis, needs analysis, expert validation results, and findings from previous LMS-based development studies relevant to vocational education. The results indicate that LMS development using the ADDIE model produces a system that is systematically designed, user-oriented, and adaptable to learners’ needs. The integration of cloud-based access and real-time online quizzes enhances learner interaction, supports immediate feedback, and promotes independent learning. The research demonstrates that IlmuOne Cloud has the potential to increase learning effectiveness, motivation, and instructional quality. The impact of this study provides a conceptual and practical reference for developing LMS-based digital learning systems in vocational schools, especially in supporting sustainable and inclusive education in the digital era.